The psychosocial impairments implicated in obesity and its relationship with bullying in two schools located in Nordeste (Research, Society and Development, 2022)
Objective: To report the experience lived during an action to promote psychosocial well-being with adolescents, focusing on bullying, obesity and eating disorders, in two schools in the cities of Aracaju and Nossa Senhora do Socorro. Methodology: This is a descriptive study of the type experience report; Five meetings were held in the morning and afternoon with students between 12 and 19 years old in two public schools in the state of Sergipe. The impressions obtained and the experience itself were analyzed based on the current literature on the subject. Each meeting was held in four stages: Presentation of the project and the intervention group; Division of students into smaller groups of 10 to 15 students to carry out a directed conversation; Conducting conversation circles with groups of 30 to 40 students on the topics: body image, bullying and obesity, focused on situations and issues that stood out at the beginning; Finally, talk to the school board to provide feedback. Results: The effectiveness and importance of activities aiming the promotion of mental health was notorious, since many students showed a lack of knowledge about various aspects of the theme, as well as interest in combating bullying. Conclusion: The action made it possible for the students to discover new concepts, deconstruct preconceived ideas and deepen their knowledge about what a healthy relationship with their own bodies would be, in addition to acting in the prevention of bullying.